Determinants of menstrual pain severity among female medical students: a cross-sectional study - Mustofa, Vina Firmanty; Aryudaningrum, Nastiti; Wulandari, Evy; Zakaria, Meylani (Universitas Ahmad Dahlan, 2025)
Dysmenorrhea, or menstrual pain, is one of the most common gynecological complaints among women of reproductive age, particularly among female students. Its impact extends beyond physical discomfort, affecting academic performance, psychological well-being, and overall quality of life. Despite its high prevalence, few studies have examined the determinants of menstrual pain severity among female medical students in Indonesia. This study aimed to identify the determinants of menstrual pain severity among female medical students at the Faculty of Medicine, Universitas Negeri Surabaya. A cross-sectional, descriptive quantitative study was conducted in November 2024, involving 112 participants selected through simple random sampling. Data were collected using a structured online questionnaire and analyzed with Spearman’s rho correlation and ordinal regression to assess associations between menstrual pain severity and independent variables, including body mass index (BMI), age at menarche, menstrual cycle characteristics, and exercise habits. Bivariate analysis indicated significant associations between menstrual pain severity and BMI (p = 0.004), age at menarche (p = 0.032), and exercise frequency (p = 0.038). However, in the adjusted multivariate regression model, only menstrual cycle length greater than 35 days remained significantly associated with increased pain severity (B = 1.143; p = 0.017). Other hypothesized predictors, including BMI, age at menarche, and exercise, did not retain independent effects after adjustment. In conclusion, irregular menstrual cycles—particularly very long cycles—were identified as the only independent determinant of increased menstrual pain severity among female students. These findings underscore the importance of considering menstrual cycle patterns when exploring risk factors for dysmenorrhea, while suggesting that commonly presumed predictors may not directly influence pain severity in this population.